The Effects of Extraction Temperature on the Physicochemical Properties of Mangrove-Derived Glucomannan (Bruguiera gymnorhiza) - Wibawanti, Jeki; Zulfanita; Norhaslinda Arun; Anang Mohamad Legowo; Sri Mulyani; Sapto Pamungkas (Science and Technology Research Centre Universitas PGRI Semarang, 2024)
This study investigates the impact of different extraction temperatures on the physicochemical properties of glucomannan derived from mangrove fruits (Bruguiera gymnorhiza). Various extraction temperatures ranging from 45°C to 85°C were utilized. Significant differences (p < 0.05) were observed in solubility (58.41% ± 2.45), total reducing sugar content (0.39% ± 0.09), yield (35.13 ± 2.95), and L* color value (71.97 ± 1.53), while no significant differences (p > 0.05) were found in a* and b* color values. These findings have implications for expanding the applications of Bruguiera and advancing research on Bruguiera glucomannan. Scanning electron microscopy (SEM) analysis revealed an increase in the cross-linking density of glucomannan molecules.